2021
DOI: 10.3390/ijms22010405
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling of Slack Channels and P2X3 Receptors Contributes to Neuropathic Pain Processing

Abstract: The sodium-activated potassium channel Slack (KNa1.1, Slo2.2, or Kcnt1) is highly expressed in populations of sensory neurons, where it mediates the sodium-activated potassium current (IKNa) and modulates neuronal activity. Previous studies suggest that Slack is involved in the processing of neuropathic pain. However, mechanisms underlying the regulation of Slack activity in this context are poorly understood. Using whole-cell patch-clamp recordings we found that Slack-mediated IKNa in sensory neurons of mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Hence, we showed in a previous study that global and sensory neuron‐specific Slack knockout mice (Slack KO) develop increased pain hypersensitivity in different models of neuropathic pain and, in addition, mice lacking Slack show altered nocifensive responses to stimulation of adenosine triphosphate (ATP)‐sensitive P 2 X 3 receptors. Inflammatory and acute nociceptive pain responses, however, were not affected by Slack deficiency 8,10,11,13,18,19 . We also demonstrated the importance of Slack for cognitive flexibility, locomotor activity, and the ability to properly adapt to unknown environments and experimental setups 6 .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Hence, we showed in a previous study that global and sensory neuron‐specific Slack knockout mice (Slack KO) develop increased pain hypersensitivity in different models of neuropathic pain and, in addition, mice lacking Slack show altered nocifensive responses to stimulation of adenosine triphosphate (ATP)‐sensitive P 2 X 3 receptors. Inflammatory and acute nociceptive pain responses, however, were not affected by Slack deficiency 8,10,11,13,18,19 . We also demonstrated the importance of Slack for cognitive flexibility, locomotor activity, and the ability to properly adapt to unknown environments and experimental setups 6 .…”
Section: Introductionmentioning
confidence: 68%
“…Inflammatory and acute nociceptive pain responses, however, were not affected by Slack deficiency. 8,10,11,13,18,19 We also demonstrated the importance of Slack for cognitive flexibility, locomotor activity, and the ability to properly adapt to unknown environments and experimental setups. 6 Moreover, male Slack KO mice showed abnormal sociability in different social interaction tests.…”
Section: Introductionmentioning
confidence: 80%
“…At a holding potential of −70 mV, a series of 500 ms-long test pulses ranging from −120 to +120 mV in intervals of 20 mV were applied. [16] Our patch-clamp recordings revealed that the developed Slack activators (except compound 2) significantly increased the I K amplitude compared to the vehicle (Figure 1B and Figure S4, Supporting Information). At a voltage of +80 mV, the current densities of the compounds increased with a range between 2.0 to 14.8 fold compared to the baseline (Figure 1B).…”
Section: Resultsmentioning
confidence: 94%
“…However, the Randall-Selitto test was used to examine the mechanical pain by measuring tail withdrawal in the previous study, for which the equipment they used was not designed (Paw Pressure Randall Selitto Instrument, IITC Life Science) ( Lu et al, 2015 ). Also, another recent study from the same group used the von Frey test to measure mechanical pain sensitivity in the parsed nerve injury (SNI) model mice and naïve mice, which showed no different mechanical pain sensitivity in naive WT and Slack –/– mice without using the Randall Selitto test ( Lu et al, 2021 ). Thus, we believe in the soundness of the enhanced response to nociceptive mechanical stimuli in Slack –/– mice.…”
Section: Discussionmentioning
confidence: 99%
“…The Slack channel is richly expressed in the brain and dorsal root ganglia (DRG) ( Bhattacharjee et al, 2002 ; Tamsett et al, 2009 ; Lu et al, 2015 ) suggesting its involvement in pain sensing. The Slack channel is also reported expressed in IB4-positive central terminals in the spinal cord ( Lu et al, 2015 ; Lu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%